Intraoperative OCT for the assessment of posterior capsular integrity in pediatric cataract surgery. Issue 3 (March 2022) - Chen, Wan; Lin, Zhuangling; Zhu, Qiaolin; Lin, Duoru; Chen, Hui; Wang, Jinghui; Chen, Jingjing; Wang, Qiwei; Wu, Xianghua; Lin, Zhuoling; Lin, Xiaoshan; Li, Xiaoyan; et al.
Abstract : In this study, the morphology of the posterior lens cortex and posterior capsules in pediatric patients with posterior lens opacities was assessed and characterized using intraoperative optical coherence tomography. Abstract : Purpose: To study the morphology of the posterior lens cortex and posterior capsules (PCs) in pediatric patients with posterior lens opacities using intraoperative optical coherence tomography (iOCT). Setting: Zhongshan Ophthalmic Center, Sun Yat-sen University, Guangzhou, China. Design: Prospective observational study. Methods: Pediatric patients with posterior lens opacities were imaged using iOCT during cataract surgery. The morphology of the posterior lens cortex and PC, along with the common patterns to indicate PC integrity, was assessed. Moreover, PC rent during surgery was observed. Results: A total of 62 eyes from 53 patients were included. The mean age of patients was 3.8 years. 4 morphological variants of posterior lens opacity were observed: type I (34/62 [54.8%]) with an intact PC; type II (20/62 [32.3%]) with an intact PC, which protruded into the anterior vitreous; type III (3/62 [4.8%]) with a deficient PC and an inability to delineate the PC; and type IV (5/62 [8.1%]) with dense opacity and an inability to characterize the posterior cortex and PC. Phacoemulsification could be performed in types I and II. In types III and IV, manual nucleus removal was performed instead of phacoemulsification. 3 cases (100%) of type III PC dehiscence developed during surgery, whereas no cases developed PC dehiscence of other types. Conclusions: The morphology of the PC and posterior lens cortex in pediatric posterior lens opacities could be categorized, and PC integrity could be assessed using iOCT, which was useful to guide surgical strategies and increase safety in pre-existing PC dehiscence in pediatric cataract surgery.